The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/am504354c
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Resistance Switching on Two-Dimensional Electron Gas

Abstract: Two-dimensional electron gas (2DEG) at the complex oxide interfaces have brought about considerable interest for the application of the next-generation multifunctional oxide electronics due to the exotic properties that do not exist in the bulk. In this study, we report the integration of 2DEG into the nonvolatile resistance switching cell as a bottom electrode, where the metal-insulator transition of 2DEG by an external field serves to significantly reduce the OFF-state leakage current while enhancing the on/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Several VCM RRAM devices have been recently reported, leveraging such 2DEG electrodes. These include Pt/ LaAlO 3 /SrTiO 3 [26], indium tin oxide (ITO)/LaAlO 3 /SrTiO 3 [28], Pt/Ta 2 O 5-y /Ta 2 O 5-x /SrTiO 3 [27], and Pt/Al 2 O 3 /SrTiO 3 [24].…”
Section: Two-dimensional Electron Gases At Oxide Interfaces For Resistive Random-access Memory Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several VCM RRAM devices have been recently reported, leveraging such 2DEG electrodes. These include Pt/ LaAlO 3 /SrTiO 3 [26], indium tin oxide (ITO)/LaAlO 3 /SrTiO 3 [28], Pt/Ta 2 O 5-y /Ta 2 O 5-x /SrTiO 3 [27], and Pt/Al 2 O 3 /SrTiO 3 [24].…”
Section: Two-dimensional Electron Gases At Oxide Interfaces For Resistive Random-access Memory Applicationsmentioning
confidence: 99%
“…Joung et al [27] reported amorphous TaO x /single crystal SrTiO 3 based VCM. Ta 2 O 5-y (TO2)/Ta 2 O 5-x (TO1) bilayer of TaO x was deposited using PLD at 200 °C under 70-100 mTorr oxygen (TO2) and at 700 °C under 0.5 mTorr oxygen (TO1).…”
Section: Two-dimensional Electron Gases At Oxide Interfaces For Resistive Random-access Memory Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seok et al reported that trimethylaluminum (TMA), an Al precursor, creates V o and electrons by reducing the TiO 2 layer, resulting in the formation of 2DEG . This laterally conducting layer formed at the Al 2 O 3 /TiO 2 interface can be interpreted as an n-type semiconductor, where V o serves as a donor, and several researchers have proposed methods to harness this 2DEG as a V o reservoir for RRAM. Thus, a more compact, scaled S-RRAM can be constructed by establishing a vertical 2DEG and employing it as an electrode and controlling the V o concentration within the RRAM layer via thermal migration from the 2DEG through a minimized active switching region.…”
Section: Introductionmentioning
confidence: 99%